Solvency Measures for Insurance Companies : Is There a Room for Improvement? - Gurenko, Eugene N.; Itigin, Alexander (World Bank, Washington, DC, 2013)
Over the last few years, there has been a considerable debate in the industry and in the academic community about the accuracy and reliability of risk-based solvency measures in approximating the level of risk retained by insurance and reinsurance entities. This topic was further reinvigorated by the recent enactment of second solvency requirements by the European Parliament, which should replace the current first solvency regulations in 2012. Despite divergence of opinions about the adequacy of specific risk based measures of required solvency capital, there seems to be a general consensus that in principle, well-designed risk based capital (RBC) or solvency requirements can help achieve an efficient reduction in the expected costs of insolvencies by helping regulators to identify weak insurers and intervene well before capital falls below specified levels. The main objective of this paper is to revisit both issues the accuracy and reliability of most common risk-based measures of insurers' solvency and the practicability of risk-based measures of solvency for corrective regulatory action. The paper also touches upon the role of financial incentives in developing the RBC estimates.